2014
DOI: 10.1309/ajcpblfbnap6n2un
|View full text |Cite
|
Sign up to set email alerts
|

Increased Concentrations of Apo A-I and Apo A-II Fragments in the Serum of Patients With Hepatocellular Carcinoma by Magnetic Beads–Assisted MALDI-TOF Mass Spectrometry

Abstract: MALDI-TOF MS analysis revealed that apo A-I is a potential novel serum marker of HCC. Combination of these pretreatments and the current magnet bead-assisted MALDI-TOF MS will further enhance the efficiency of biomarker discovery for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Liu et al [24] recorded results similar to us and stated that Apo A2 at cutoff level > 107 mg/dL with sensitivity 13% and specificity 96% to differentiate a case of HCC from cirrhotic HCV patient. Our study showed that IGF1 and IGF1R were not able to differentiate a case of HCC from cirrhotic HCV which was agreed by Jiang et al [25] who denied the diagnostic value of IGF1 and IGF1R in ruling out a case of HCC. In our study, alpha-fetoprotein at cutoff value > 48 ng/dL can differentiate a case of HCC from cirrhotic HCV with sensitivity 69.2%, specificity 71.9%, PPV 80%, NPV 95% and TA 70.2%.…”
Section: Discussionsupporting
confidence: 60%
“…Liu et al [24] recorded results similar to us and stated that Apo A2 at cutoff level > 107 mg/dL with sensitivity 13% and specificity 96% to differentiate a case of HCC from cirrhotic HCV patient. Our study showed that IGF1 and IGF1R were not able to differentiate a case of HCC from cirrhotic HCV which was agreed by Jiang et al [25] who denied the diagnostic value of IGF1 and IGF1R in ruling out a case of HCC. In our study, alpha-fetoprotein at cutoff value > 48 ng/dL can differentiate a case of HCC from cirrhotic HCV with sensitivity 69.2%, specificity 71.9%, PPV 80%, NPV 95% and TA 70.2%.…”
Section: Discussionsupporting
confidence: 60%
“…A number of these candidate biomarkers were reported as HCC‐related biomarkers in previous studies. Among the candidate biomarkers found in both cohorts, five upregulated proteins were reported in previous HCC studies, namely, apolipoprotein A‐II (APOA2, P02652) , clusterin (CLU, P10909) , complement factor B (CFB, P00751) , serum amyloid P‐component (APCS, P02743) , and vitronectin (VTN, P04004) . Alteration of proteins of biofluids in HCC compared with cirrhosis may potentially contribute to diagnostic signatures for HCC.…”
Section: Resultsmentioning
confidence: 78%
“…MALDI-TOF-MS analysis can precisely separate and identify target proteins or peptides according to their mass-dependent velocities (m/z) (Ketterlinus et al 2005). It has recently been wildly applied to the diagnosis of cancer, such as prostate cancer (Villanueva et al 2006), oral cancer (Cheng et al 2005), thyroid cancer (Villanueva et al 2006), hepatocellular carcinoma (Liu et al 2014), bladder cancer (Schwamborn et al 2009), breast cancer (Hamler et al 2004), head-andneck squamous cell carcinoma (Jarai et al 2012), glioblastoma (Kumar et al 2010) and colorectal cancer (Deng et al 2013).…”
Section: Discussionmentioning
confidence: 99%